ROLE OF CARE ORPHANIC CARE IN FORMING INDEPENDENCE OF CHILDREN IN MUSTIKA TAMA ORPHANAGE IN BANTUL DISTRICT - Putri, Eka Cahyati; Perianto, Eko (Universitas Teknologi Yogyakarta, 2020)
This study aims to determine the role of caregivers in configuring children's independence in Mustika Tama orphanages in Bantul in year 2020.Data were collected from documentation, observations, and interviews with caregivers and foster children at Mustika Tama orphanage. The data obtained then analyzed using qualitative descriptive methods with steps of data reduction, data presentation, and drawing conclusions and testing the validity of the data using Triangulation method.Based on the results of the study, it was found that the role of caregivers was crucial to the formation of independence in the children's at Mustika Tama orphanage. Caregivers have a role to guide, educate, care for, love affectionately and provide high motivation to children. The role of caregivers in configuring children's independence is influenced by inhibiting and supporting factors. Inhibiting factors such as: the characteristics of different children, children are likely to go along and stubborn. The supporting factor is that the facilities provided by the management to the caregiver are maximized.